Similar outcomes including maximum knee flexion between mobile bearing condylar‐stabilised and fixed bearing posterior‐stabilised prosthesis: a case control study - Jobe Shatrov; Elliot Sappey‐Marinier; Moussa Kafelov; Stanislas Gunst; Cécile Batailler; Elvire Servien; Sébastien Lustig (Journal of Experimental Orthopaedics, 2022)
Abstract Purpose Prosthesis design influences stability in total knee arthroplasty and may affect maximum knee flexion. Posterior‐stabilised (PS) and condylar‐stabilised (CS) designed prosthesis do not require a posterior‐cruciate ligament to provide stability. The aim of the current study was to compare the range of motion (ROM) and clinical outcomes of patients undergoing cemented total knee arthroplasty (TKA) using either a PS or CS design prosthesis. Methods A total of 167 consecutive primary TKAs with a CS bearing (mobile deep‐dish polyethylene) were retrospectively identified and compared to 332 primary TKA with a PS constraint, with similar design components from the same manufacturer. Passive ROM was assessed at last follow‐up with use of a handheld goniometer. Clinical scores were assessed using Patient‐Reported Outcome Measures (PROMs); International Knee Society (IKS) knee and function scores and satisfaction score. Radiographic assessment was performed pre and post operatively consisting of mechanical femorotibial angle (mFTA), femoral and tibial mechanical angles measured medially (FMA and TMA, respectively) on long leg radiographs, tibial slope and patella height as measured by the Blackburne‐Peel index (BPI). Results Both groups had a mean follow‐up of 3 years (range 2–3.7 years). Mean post‐operative maximum knee flexion was 117° ± 4.9° in the PS group and 119° ± 5.2° in the CS group (p = 0.29). Postoperative IKS scores were significantly improved in both groups compared to preoperative scores (p < 0.01). The mean IKS score in the PS group was 170.9 ± 24.1 compared to 170.3 ± 22.5 in the CS group (p = 0.3). Both groups had similar radiographic outcomes as determined by coronal and sagittal alignment, tibial slope and posterior condylar offset ratio measurements. When considering the size of tibial slope change and posterior‐condylar offset ratio, there was no differences between groups (p = 0.4 and 0.59 respectively). The PS group had more interventions for post‐operative stiffness (arthrolysis or manipulation under anaesthesia) 8 (2.7%) compared to 1 (0.6%) in the CS group (p = 0.17). Conclusion Condylar‐stabilised TKA have similar patient outcomes and ROM at a mean follow‐up of 3 years compared to PS TKA. Highly congruent inserts could be used without compromising results in TKA at short term. Level of evidence Level IV, retrospective case control study.